P226 Systematic review with meta-analysis of individual data: impact of cut-off values on the performance of faecal calprotectin to detect endoscopic recurrence after intestinal resection in patients with Crohn's disease. (25th January 2019) - Kirchgesner, J; Boschetti, G; Buisson, A; Yamamoto, T; Domenech, E; Nancey, S; Peyrin-Biroulet, L; Uzzan, M
Abstract: Background: Endoscopic assessment of post-operative recurrence (ePOR) is recommended within 1 year after ileocaecal resection (ICR) for Crohn's disease (CD) as it accurately predicts clinical course and guides medical management. However, endoscopy is an invasive procedure and a frequent endoscopic monitoring is not feasible in routine care. Although faecal calprotectin (FC) has been studied and validated as a useful tool in CD in several settings, it is still not well defined how thresholds impact the performance of FC to detect ePOR. In this meta-analysis including cohort studies of CD patients who underwent intestinal resection, we aimed to determine how cut-off values influence the performance of the FC to detect ePOR. Methods: A systematic search using PubMed and EMBASE databases was performed independently by two authors. The search strategy used the following terms: calprotectin, Crohn's, Ileocaecal, postop*, intestinal resection. Studies performed in adult patients with CD who underwent intestinal resection, in which FC (expressed in µg/g) was evaluated as a surrogated marker of ePOR (defined as a Rutgeers score ≥ i2 or i2b) were included. The extracted data were pooled using a hierarchical summary receiver-operating curve model. We assessed the sensitivity, specificity and positive and negative likelihood ratios for FC cut-offs ranging from 10 µg/g to 500 µg/g. Results: A total of 158 titles and abstracts were identified. After selection, 11 studies remained for further analysis. A total of 892 patients were included, among whom 421 (47.2%) developed ePOR. Eight studies were designed as cross-sectional studies with either a retrospective or a prospective selection of patients. Two studies were a sub analysis of randomised control trials (POCER and TOPPIC). For FC cut-offs set at 50 µg/g and below, the sensitivity to detect ePOR was at least of 0.92. Specifically for 50 µg/g, it was estimated at 0.92 (95% confidence interval (95CI) [0.85–0.96]). On the other hand, a cut-off at 250 µg/g or more provided a specificity of at least 0.90 to detect ePOR (0.90 95CI[0.79–0.96] for 250 µg/g). Sensitivity and specificity of FC to detect ePOR according to cut-off. Conclusions: After ICR for CD, FC outside a 50–250 µg/g range could avoid unnecessary colonoscopies, as it allows the detection with a high probability of endoscopic remission (< 50 µg/g) or ePOR (>250 µg/g).